Novel Positron Emission Tomography Probes Specific for Deoxycytidine Kinase - Shu, Chengyi J. (2010)
Deoxycytidine kinase (dCK) is a rate-limiting enzyme in the deoxyribonucleoside salvage pathway and a critical determinant of therapeutic activity for several nucleoside analog pro-drugs. We have previously reported the development of (18)F-FAC, (1-(2′-deoxy-2′-(18)F-fluoro-β-D-arabinofuranosyl) cytosine), a new probe for PET imaging of dCK activity in immune disorders and certain cancers. The objective of the current study was to develop PET probes with improved metabolic stability and specificity for dCK. Towards this goal, several candidate PET probes were synthesized and evaluated in vitro and in vivo. METHODS: High pressure liquid chromatography was used to analyze the metabolic stability of (18)F-FAC and of several newly-synthesized analogs with the natural D-enantiomeric sugar configuration or the corresponding unnatural L-configuration. In vitro kinase and uptake assays were used to determine the affinity of the (18)F-FAC L-nucleoside analogs for dCK. The biodistribution of selected L- analogs in mice was determined by microPET/CT imaging. RESULTS: Candidate PET probes were selected using the following criteria: low susceptibility to deamination, high affinity for purified recombinant dCK, high uptake in dCK expressing cell lines and biodistribution in mice reflective of the tissue expression pattern of dCK. Amongst the ten newly-developed candidate probes, 1-(2′-deoxy-2′-(18)F-fluoro-β-L-arabinofuranosyl) cytosine (L-(18)F-FAC) and 1-(2′-deoxy-2′-(18)F-fluoro-β-L-arabinofuranosyl)-5-methylcytosine (L-(18)F-FMAC) most closely matched the selection criteria. The selection of L-(18)F-FAC and L-(18)F-FMAC was validated by showing that these two PET probes can be used to image animal models of leukemia and autoimmunity. CONCLUSION: Promising in vitro and in vivo data warrant biodistribution and dosimetry studies of L-(18)F-FAC and L-(18)F-FMAC in humans.